PEMBENTUKAN, PERKEMBANGAN DAN PEMBAHARUAN HUKUM ISLAM DALAM TINJAUAN KAUM ORIENTALIS - Fachruddin, Fachruddin (DE JURE, 2012)
The development of Islamic law from its inception to its maturity has drawn a lot  of  attentions from some well known figures within Western scholars. Great names, such as Goldziher, Schacht, and Anderson, are among those who contribute the discourses on Islamic law in classical and modern period. While the first two scholars focus their research on Islamic law in the early phase of its development, the last one direct his study on its development in the modern period. The role of Quran and Sunnah on the development of Islamic law is under critical analysis of the Goldziher and Schacht, while the reform of it becomes the center of Anderson’s study.Keywords: Orientalis, Pembaharuan, Hukum Islam